Kosztolányi és Ady költészetértelmezésének összefüggései - Gintli, Tibor (Studia Litteraria, 2018)
Endre Ady and Dezső Kosztolányi are two distinguished poets of modern Hungarian literature. Although their poetic self-interpretation and practice shownumerous differences, they both interpret poetry in a metaphysical context. While Ady represents the modern version of the prophet poet’s archaic role, Kosztolányi considers the transcendent sphere exclusively as a fiction created within the stretch of the poem. Therefore Kosztolányi regards all interpretations about the role of the poet as a self-betrayal which considers the poet as a medium who may get an insight into the actually existing metaphysical world.